2015
DOI: 10.4187/respcare.03753
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Utility of Biomarkers in COPD

Abstract: BACKGROUND: COPD will become the third leading cause of death by 2020. There are many situations in which spirometry, the primary tool for diagnosis of COPD, cannot be performed, and thus, the staging and status of these patients cannot be determined. To date, there is no known biochemical marker used for diagnosing COPD. This study aimed to explore the utility of biomarkers for diagnosis of COPD. METHODS: This was an observational study composed of 96 stable subjects with COPD and 96 subjects with normal lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 75 publications
(69 reference statements)
0
22
1
1
Order By: Relevance
“…Females showing higher serum glutathione peroxidase activity (256.4 Ϯ 10.4 U/L vs 222.8 Ϯ 15.6 U/L, P Ͻ .05) than males have been reported by Rush and Sandiford. 2 However, the possibility of attributing the higher glutathione peroxidase activity measured in our study 1 is attributable to a predominantly female rather than male population, as suggested by the author, may not be relevant. What we have highlighted in this study is a difference in the levels of glutathione peroxidase in the control group (50.95 Ϯ 15.30 U/L) as compared with the COPD group (89.73 Ϯ 27.84 U/L).…”
Section: Serum Biomarkers Of Copd-replycontrasting
confidence: 39%
See 2 more Smart Citations
“…Females showing higher serum glutathione peroxidase activity (256.4 Ϯ 10.4 U/L vs 222.8 Ϯ 15.6 U/L, P Ͻ .05) than males have been reported by Rush and Sandiford. 2 However, the possibility of attributing the higher glutathione peroxidase activity measured in our study 1 is attributable to a predominantly female rather than male population, as suggested by the author, may not be relevant. What we have highlighted in this study is a difference in the levels of glutathione peroxidase in the control group (50.95 Ϯ 15.30 U/L) as compared with the COPD group (89.73 Ϯ 27.84 U/L).…”
Section: Serum Biomarkers Of Copd-replycontrasting
confidence: 39%
“…1 First of all, I could not understand the meaning of the sentence "Prior studies have reported that plasma glutathione peroxidase levels were significantly elevated in plasma than males." I believe that the author of the letter wants to reflect higher serum glutathione peroxidase levels in females as compared with males.…”
Section: Serum Biomarkers Of Copd-replymentioning
confidence: 96%
See 1 more Smart Citation
“…Estimating SOD with an ELISA kit, a significant reduction has been found in COPD subjects compared to controls [105] (Table 1). …”
Section: Introductionmentioning
confidence: 99%
“…Обсуждается роль уско-ренного старения, развитие аутофагии при острых и хронических заболеваниях легких [13][14][15], пред-лагаются многочисленные биомаркеры для клиниче-ского использования при ХОЗЛ [16][17][18], которые в Фенотипы ХОЗЛ -путь к персонифицированной медицине ХХI века сочетании с показателями состояния легочной ткани позволят сделать новые шаги в фенотипировании. Следует заметить, что большинство существующих ныне биомаркеров не являются специфичными для ХОЗЛ [19], и сегодня их исследование зачастую не-доступно для практикующих врачей.…”
unclassified